The Psychometric Properties of the Positive and Negative Suicidal Ideation Scale among Portuguese Young Adults - Marta Brás; João Antunes; Cláudia Carmo (European Journal of Investigation in Health, Psychology and Education, 2024)
Preventing suicide has been a worldwide imperative for the last decade. Accurately assessing suicide risk is the first step towards prevention, and access to reliable tools that measure risk factors is essential to achieve this goal. The Positive And Negative Suicidal Ideation (PANSI) scale is a validated brief suicidal ideation scale that could prove useful to this goal due to its ability to measure both suicide risk and protective factors. The PANSI scale has been adapted to various languages and cultures across various clinical and non-clinical populations. Despite this, no Portuguese has been produced yet. The present study aimed to validate a Portuguese version of PANSI by evaluating its psychometric properties in a sample of 259 young adults. Confirmatory factor analysis showed that the PANSI showed good psychometric properties (TLI = 0.95), good reliability for positive ideation (α = 0.84), and excellent reliability for negative ideation (α = 0.96). The scale also showed good discriminative ability through prediction of a previous suicide attempt and good construct validity in both subscales. The Portuguese adaptation of the PANSI scale is a reliable measure of positive and negative suicidal ideation that could prove useful in both clinical and research settings.